Colonial and contemporary Bihar and Jharkhand - Singh, Lata (Ratna Sagar New Delhi, 2013)
This book tries to capture the complexities of some of these diverse movements. The articulation of backward castes and tribal protests have been problematized by the emergence of internal hierarchies, differentiations and contestations. The predicament of ethnic identity and culture in the face of unrestrained globalizing forces in the tribal belt is also a matter of concern. Bihar and Jharkhand also have a rich popular/subaltern culture, which has been overshadowed and eclipsed in most of the scholarly work on this region. This book highlights how popular culture and oral cultural traditions emerged as a site for multiple articulations-articulation of marginalization, as well as resistance and subversion. This collection of essays will appeal to those interested in social history, political and cultural studies and the world of the poor and the marginalized.
Bib and Ref
Keywords: India History British occupation, 1765-1947; Jharkhand (India) History 19th century; Jharkhand (India) History 20th century